The Effect of Debt To Equity Ratio, Current Ratio, Return On Equity on the Company's Share Price PT.Indofood Sukses Makmur Tbk - Vevi Ariyanti; Hartono; Yuliasnita Verlandes (CV Putra Publisher, 2023)
Stock prices in the capital market fluctuate which also causes ups and downs of investor interest to invest in the company. These rates vary from time to time depending on the performance of the Company. Stock prices rise when there is excess demand. However, stock prices also fall when there is excess demand. Therefore, the performance of a company affects the high share price of the company PT.Indofood Sukses Makmur Tbk. The solvency ratio is a ratio that measures how much a company's assets are financed by debt. Part of the solvency ratio included in research material is the ratio of debt to equity. The debt to equity ratio shows how much the equity to debt ratio is used to capitalize the company's assets. The liquidity ratio is an asset that is used in a market that functions in such a way that, the result can be quickly converted into money at the current market price. The higher the current ratio, the better the company's liquidity. The profitability ratio is seen as the influence of the company's stock price as a percentage of return on equity (ROE). ROE measures the return received by company owners (shareholders) from any capital paid to the company in the form of dividends. The research data used is in the form of secondary data in the form of the financial statements of the company PT.Indofood Sukses Makmur Tbk which have been published on the Indonesia Stock Exchange for the period 2015-2019. The sample for this study was 5 financial statements of the company PT.Indofood Sukses Makmur Tbk using a sample determination technique, namely total sampling. The data analysis technique used analysis with the help of the SPSS 25 program. The results showed that the DER variable had a negative and insignificant effect on stock prices, the CR variable had a negative and insignificant effect on stock prices. And the ROE variable had a positive and significant effect on stock prices. the company's share price PT.Indofood Sukses Makmur Tbk.